Avaliação do perfil dos egressos dos cursos de Medicina da UNIFENAS - Campus Alfenas e Belo Horizonte - DUARTE, Marynês Zaparoli (2019)
Introduction: The project aimed to evaluate the profile of undergraduate students of the medical programs os UNIFENAS, Campus Alfenas (UA) and Belo Horizonte (BH). Studying undergraduate students in one of the ways of evaluating the impact of programs in the training of health professinals, which can contribute to curriculum improvement. Objective: To draw the degree of satisfaction of undergraduate students regarding their programs and their insertion in the job market. Methods: It was a quantitative survey, conducted through na eletronic questionnaire elaborated with Google Forms and available in Google Docs. The questionnaire was sent to undergraduate students whose eletronic addresses were provided by CRM MG, the academic department of programs,and professors’ database. From the 2,409 undergraduate students of Alfenas, between 1994 and 2017, eletronic addresses were found of 1,346 (55,8%), of which 482 (35,8%) answered the questionare. In Belo Horizonte, from the 1,033 undergraduate students, between 2003 and 2008, it was found 742 eletronic addresses of undergraduate students (71,8%), of which 148 (19,9%) have responded. This represented 20% of all undergraduate students from the Alfenas program and 14,3% of all undergraduate students from the Belo Horizonte program. The majority consisted of women, with na average age of 32 years old, and from cities in the southeast of the country. Results: Most of the undergraduate students from UNIFENAS UA and UBH work in cities in the countryside, in the southeast region, with a higler internalization rate of medical work in the UA. The initial job of said undergraduate students was in basic health system units or in medical emergencies units (ERs). The approval rate for medical residency was satisfactory and doing preparatory courses for admission into the selective process did not make any difference. More than 80% of the undergraduate students act exclusively on medical activity and, in their vast majority, they received more than R$ 10,000 Brazilian Reais a month. They also said to be satisfied with their area of medical practice, and the most frequent acting areas were: Meical Clinic, Gynecology-Obstretics, Pediatrics, General Surgery and Anesthesiology. From the undergraduate students who did not complete the medical program in 12 semesters, most claimed failling courses during the program as the main cause. Conclusion: The majority reported that they were satisfied with their profession and considered that their medical education was satisfactory. There was a tendency for better assessments among the undergraduate students of the UA and among students who have gotten their degree longer ago, regardless of the campus reseasched. Medical Clinic, Pediatrics and Collective Health were areas in the which the undergraduate students felt better trained